Evaluation of depression, anxiety, and stress among university healthcare students - Rina Tripathi,, Saad S. Alqahtani,, Abdulkarim M. Meraya,, Hafiz A. Makeen,, Pankaj Tripathi,, Shyam Sunder Pancholi (Journal of Applied Pharmaceutical Science, 2022)
Mental health disorders in university healthcare students represent a leading cause of disability and a growing public health concern. This study aimed to assesses the prevalence of depression, anxiety, and stress (DAS) among undergraduate healthcare students and examine the stress triggers and alleviators. A cross-sectional study was conducted among 473 students of medical, dental, nursing, and pharmacy programs of Jazan University, Saudi Arabia, using a pretested sociodemographic questionnaire based on the Depression, Anxiety, and Stress Scale (DASS-21). Chi-square test and multivariable logistic regression analysis were used to assess the factors associated with DASS- 21 using Stata 15. The overall prevalence of DAS was high among healthcare students. Medical students reported significantly high depression, whereas anxiety and stress were high among dental students. Female students scored significantly high depression and anxiety on DASS. High cumulative grade point average (CGPA) and high body mass index (BMI) were found directly associated with DAS. The key stress trigger was academic burden, while emotional support was preferred alleviator. Our findings revealed that the psychological well-being of healthcare students is at risk. Gender, CGPA, and BMI appears to impact overall mental health. Intervention targeted to minimize psychological burden of healthcare undergraduates is warranted.
Keywords: Depression, anxiety, stress, DASS-21, healthcare students, Saudi Arabia